A Concise Literature Review on Niosome Drug Delivery from Ancient to Recent (Asian Journal of Pharmaceutics (AJP), 2023)
About 50% of medications/drugs have obstacle of poor solubility, poor oral bioavailability, due to enzymatic/gastricdegradation in the gastrointestinal tract pH, high pre-systemic intestinal and hepatic metabolism, permeability,small absorption window, and short residence duration at the absorption location. Niosomal drug deliveries havespecific advantages over conventional dosage form with respect to improvement in bioavailability. Niosomes arecolloidal particles created when non-ionic surfactants self-assemble in an aqueous solution to form closed bilayerstructures. The various methods are reported until today for the preparation of niosomes; ether injection method,thin film hydration method, sonication method, microfluidization, multiple membrane extrusion method, reversephaseevaporation technique, transmembrane Ph. Gradient drug uptake process (remote loading), the bubblemethod, freeze-thaw method, emulsion method, and formation of niosomes from proniosome. The current reviewarticle focused on the preparation and evaluation of niosome drug delivery and its advantages over conventionaldrug delivery. The niosomal drug delivery was found to be best for solubility and bioavailability enhancement ofpoorly water-soluble drugs.